MUSICâ€: A STRESS RELIEVING FACTOR IN PATIENTS UNDERGOING DENTAL SURGERIES - S, Jembulingam; Priya A, Jothi; R, Gayatri (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Music is one of the inexpensive, safe, and non-pharmacological stress-reducing factors. Various surgeries increase the stress levels of the patient by increasing their blood pressure and anxiety level. This change in blood pressure can be lowered by certain safe and non-invasive techniques. One of the significant techniques is to listen to music. Hence, the objective of this study is to validate the fact that music help acts a stress relieving factor by decreasing the blood pressure of the patient who is undergoing dental surgeries. Methods: About 20 participants were selected for the study; out of which, 15 participants participated in this study, and others were excluded as they did not meet the inclusion criteria. The blood pressure was calculated at rest position before the surgery, and then pleasant soft music was played to the patient during the surgery. Then, the blood pressure was measured at an interval of 5 minutes for a span of 15 minutes. The observed blood pressure was recorded. Statistical analysis was done with the recorded data in Statistical Package for the Social Sciences Software (version 20). Results: Initially, the blood pressure of the patient was found to be at a mean level of 107/65 mmHg which rose to a greater heights of 116/68 mmHg which then lowered down to a mean level of 108/61 mmHg at the end of 15 minutes after the music was played to the patient during the surgery. Conclusion: This study can conclude by saying that pleasant and soft music has an ability to stabilize the systolic blood pressure of patients undergoing dental surgeries. Keywords: Systolic blood pressure, Music, Stress, Dental surgeries, Stress busters, Soft music.